Plastic deformation instabilities in Bi crystals under microindentation - Rogacheva, E.I.; Yakovleva, A.A.; Lyubchenko, S.G. (Functional Materials, 2005)
The dependences of microhardness Н on the load on indentor were obtained for bismuth single- and polycrystals. The general tendency to Н decreasing with Р increasing up to
~ 0.15 N is observed. After that the microhardness practically does not change. In the range of Р - 0,05-0,15 N, in the Н(Р) dependences the oscillations are detected whose presence is explained by qualitative changes in plastic deformation micromechanisms and in the crystal defect structure under increasing indentor load. Получены зависимости микротвердости Н моно- и поликристаллов висмута от величины нагрузки на индентор Р. Наблюдается общая тенденция к снижению Н с увеличением Р до ~0,15 N, после чего микротвердость практически не изменяется. В интервале Р - 0,05-0,15 N на зависимостях Н(Р) обнаружены осцилляции, наличие которых связывается с качественными изменениями в микромеханизмах пластической деформации и в дефектной структуре кристалла при увеличении нагрузки на индентор. Одержано залежностi мiкротвердостi Н моно- та полiкристалiв вiсмуту вiд величини навантаження на iндентор Р. Cпостерiгається загальна тенденцiя до зниження Н при зростаннi Р до ~0,15 N, пiсля чого мiкротвердiсть практично не змiнюється. В iнтервалi Р - 0,05-0,15 N на залежностях Н(Р) виявляються осциляцii, наявнiсть яких
пов'язується з якiсними змiнами у мiкромеханiзмах пластичної деформацiї та у дефектнiй структурi кристала при зростаннi навантаження на iндентор.